농가유형별 생산기술효율 및 환경성과 비교분석 - 김은순 (한국농촌경제연구원, 2003)
Technical Efficiency with Environmentally Detrimental Outputs in Korean Farms A nonparametric analysis is utilized to estimate technical efficiency with agricultural pollution as bad outputs based on recent 5 year's raw data for Korean farms. Output technical efficiency measure is decomposed into net technical efficiency, scale efficiency, and environmental efficiency. Environmental efficiency or the loss of production is measured when environmental regulation or pollution reduction process incurs technological constraint in the process of production. Over the recent 5 years(1998-2002), average technical efficiency under no technical constraint is 0.5 or so, which implies about 50% technical inefficiency exists overall including all types and levels of Korean farms. Large scale farms are more technically efficient than small farms. Output scale effciency is measured 0.76～0.92 for large farms and 0.92～0.95 for small farms, where the scale inefficiency is due to increasing returns to scale for most Korean farms. Hence 5-24% of average costs can be saved with enlargement of farm size. The gaps of technical efficiency between small farms and large farms get bigger, which implies small farms get less technically efficient than large farms. Environmental efficiency is increased when technical efficiency decreased as expected. Environmental constraints in the process of production is measured to bring about 3% decrease of agricultural production in general, implying that amount of more than 3% of total agricultural output needs to be subsidized as an incentive for voluntary reduction of agricultural pollution by farmers. Researchers: Gim Uhn-Soon E-mail Address: uhnskim@krei.re.kr